The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3389/fnsyn.2016.00007
|View full text |Cite
|
Sign up to set email alerts
|

SNAP-25, a Known Presynaptic Protein with Emerging Postsynaptic Functions

Abstract: A hallmark of synaptic specializations is their dependence on highly organized complexes of proteins that interact with each other. The loss or modification of key synaptic proteins directly affects the properties of such networks, ultimately impacting synaptic function. SNAP-25 is a component of the SNARE complex, which is central to synaptic vesicle exocytosis, and, by directly interacting with different calcium channels subunits, it negatively modulates neuronal voltage-gated calcium channels, thus regulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
91
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(95 citation statements)
references
References 107 publications
(118 reference statements)
4
91
0
Order By: Relevance
“…Neurons function depends on the synaptic transmission, in which synapse density proteins play a key role; in AD several studies showed synapses dysfunction and loss to occur before neurons loss, thus attention has been paid to synapse-associated proteins, such as PSD-95 and SNAP-25. PSD-95 is a postsynaptic scaffolding protein that regulates synaptic distribution and activity of glutamate receptors (Tu et al, 2014); SNAP-25 is a component of the SNARE complex, which is central to synaptic vesicle exocytosis, and, by directly interacting with different calcium channels subunits, it negatively modulates neuronal voltage-gated calcium channels, thus regulating intracellular calcium dynamics (Antonucci et al, 2016). SH-SY5Y cells express both synaptic proteins, among others, and reduced levels of these synaptic proteins is expected to alter the cells function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurons function depends on the synaptic transmission, in which synapse density proteins play a key role; in AD several studies showed synapses dysfunction and loss to occur before neurons loss, thus attention has been paid to synapse-associated proteins, such as PSD-95 and SNAP-25. PSD-95 is a postsynaptic scaffolding protein that regulates synaptic distribution and activity of glutamate receptors (Tu et al, 2014); SNAP-25 is a component of the SNARE complex, which is central to synaptic vesicle exocytosis, and, by directly interacting with different calcium channels subunits, it negatively modulates neuronal voltage-gated calcium channels, thus regulating intracellular calcium dynamics (Antonucci et al, 2016). SH-SY5Y cells express both synaptic proteins, among others, and reduced levels of these synaptic proteins is expected to alter the cells function.…”
Section: Discussionmentioning
confidence: 99%
“…SH-SY5Y cells express both synaptic proteins, among others, and reduced levels of these synaptic proteins is expected to alter the cells function. Several studies reported that Aβo lead to down-regulation in synaptic markers (Leuba et al, 2008, Feng et al, 2014, Fernandes et al, 2017), and the loss or modification of synaptic proteins directly affects their properties, ultimately impacting synaptic function (Antonucci et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…SNAP‐25tot did not show any change over time, whereas SNAP‐25aa40 followed the same pattern as GAP‐43, NFL and tau, but it was not significantly altered. This could be due to that SNAP‐25 is expressed in both presynaptic and postsynaptic parts of the neuron, and therefore, the pattern is not as clear in CSF . Nevertheless, considering the function of SNAP‐25aa40 and the trend towards an increase, our data suggest a possible role in recovery after cranial irradiation.…”
Section: Discussionmentioning
confidence: 77%
“…SNAP‐25 and SYT1 are part of or interact with the SNARE complex and play a key role in protein and membrane trafficking, hormone secretion and neurotransmitter release. SNAP‐25 has been shown to be involved in spine maturity . For example, Tomasoni et al .…”
Section: Discussionmentioning
confidence: 99%
“…Its anchoring is due to the palmitoylation of four cysteines located in the center of the protein chain. There are several isoforms of SNAP-25, for example, SNAP-29 and SNAP-23; all are involved in the regulation of exocytosis phenomena [37]. …”
Section: Botulinum Toxinmentioning
confidence: 99%